3-Dimensional computed tomographic assessment predicts conduction block and paravalvular leakage after rapid-deployment aortic valve replacement. (23rd October 2021) - Park, Sung Jun; Rhee, Younju; Lee, Chee-Hoon; Kim, Ho Jin; Kim, Joon Bum; Choo, Suk Jung; Lee, Jae Won
Abstract: OBJECTIVES: Complications like complete atrioventricular block (CAVB) and paravalvular leakage (PVL) following rapid deployment aortic valve (AV) replacement (RDAVR) remain unresolved. Selecting an optimal size of the valve might be important to minimize the incidence of these complications. We sought to determine the impact of prosthesis size relative to the anatomic profile of the AV on the occurrence of CAVB or PVL after RDAVR. METHODS: Preoperative computed tomographic (CT) images were evaluated in patients receiving RDAVR (INTUITY ELITE) between February 2016 and December 2019. The occurrence of CAVB requiring permanent pacemaker implantation and PVL (≥ mild) was evaluated. The relative size of implants against the cross-sectional dimensions of recipients' AV annulus and left ventricular outflow tract (LVOT) were calculated. RESULTS: Among 187 eligible patients, CAVB and PVL (≥ mild) occurred in 12 (6.4%) and 11 patients (5.9%), respectively. CAVB was associated with oversized RDAVR (RDAVR frame width minus average diameter of LVOT calculated from the cross-sectional area [ΔLVOTarea ]: odds ratio, 2.05; 95% confidence interval, 1.28–3.30): this was with an area under the curve of 0.78 ( P = 0.005). The projected probability of CAVB was <3% when the ΔLVOTarea was <1.3. In contrast, PVL was associated with under-sized RDAVR (RDAVR size divided by the longest diameter of AV annulus [index Annlong ]: odds ratio, 0.64; 95% confidence interval, 0.51–0.79): This was with an area under curve of 0.94 ( P < 0.001). CONCLUSIONS: CT parameters of the AV annulus and LVOT are highly reliable in the prediction of CAVB or PVL after RDAVR. Our data might justify CT-based sizing of prosthesis for RDAVR. Abstract : Conventional surgical aortic valve (AV) replacement (AVR) has been the gold standard for the treatment of severe AV disease for the past 50 years [1].